Phytochemical Isolation, Characterization, And Biological Evaluation Of Dye-Yielding Plants - Vipul Kumar; Dr Jigar Y. Soni; Dr Gitam singh (Revista Electronica de Veterinaria, 2024)
Natural dyes derived from plants have long been used in traditional textile dyeing, food coloring, and medicinal applications. Due to the growing environmental and health concerns associated with synthetic dyes, there is an increasing global interest in the revival and scientific exploration of plant-based dyes. This review provides a detailed overview of the phytochemical isolation, structural characterization, and biological assessment of compounds obtained from various dye-producing plants. It summarizes recent advancements in extraction techniques, chromatographic isolation methods, and spectroscopic tools used to identify bioactive compounds. Additionally, the review highlights the biological potentials of these natural dyes, including their antioxidant, antimicrobial, anticancer, and anti-inflammatory activities. The findings support the significance of dye-yielding plants as valuable sources of eco-friendly colorants with potential therapeutic benefits.